V.l.n.r.: Albers, Rijnvis, Matthes, Molhoek. Het ondertekenen van de fusie tussen SHV en RAET - Troost, Roel,
V.l.n.r.: Albers, Rijnvis, Matthes, Molhoek. Het ondertekenen van de fusie tussen SHV en RAET.